TRIZ trend of engineering system evolution: A review on applications, benefits, challenges and enhancement with computer-aided aspects. (December 2022) - Ghane, Mostafa; Ang, Mei Choo; Cavallucci, Denis; Kadir, Rabiah Abdul; Ng, Kok Weng; Sorooshian, Shahryar
Highlights: Trend of Engineering System Evolution (TESE) as a popular tool in TRIZ is demonstrated. Benefits and limitations of TESE plus its current improvement is illustrated. Recommendations for improvement of TESE were derived in addressing the existing limitations. Abstract: Trend of Engineering system evolution (TESE) is a popular tool in the theory of inventive problem-solving (TRIZ). Because it is applicable in various domains, it has been extensively used in practical projects to develop engineering products and forecast new technologies. However, although its generic pattern makes it a versatile tool for inventing and discovering the next generation of engineering systems, the scope of its practical use in product innovation has yet to be critically explored. This includes the applicability of its trends and sub-trends, efficacy and benefits in product development, and challenges and limitations. Therefore, this review uses reliable and noteworthy studies to overview the use of TESE in science and explore the benefits and challenges associated with its practical use. TESE-based studies have been conducted to prove its usability in technological development and innovation. We recommend that TESE should be integrated with various computer-aided aspects, such as scientific information, patents, social networking, disruptive technologies, manufacturing, and robotics, to address existing limitations. In addition, this review validates that these five aspects have yet to be demonstrated cohesively. This review provides TESE practitioners with insights into the application of the trends and sub-trends of the TESE toolkit.